2019
DOI: 10.1039/c9cy01471c
|View full text |Cite
|
Sign up to set email alerts
|

One step phenol synthesis from benzene catalysed by nickel(ii) complexes

Abstract: Nickel(ii)complexes of N4-ligands are reported as efficient catalysts for direct benzene hydroxylation via bis(μ-oxo)dinickel(iii) intermediate species. The exclusive phenol formation is achieved with a yield of 41%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…Toluene was oxidized to para ‐cresol in 22% yield, together with ortho ‐cresol and methyl‐ para ‐benzoquinone in 8 and 1% yield, respectively (Table 3, entry 3). Recent studies on aromatic oxidations have shown other complexes to be capable of oxidizing the aromatic ring of toluene as well, showing however significant amounts of aliphatic oxidation towards benzyl alcohol or benzaldehyde products [3g,4a,b,e,f] . Remarkably, Mn( tips bpmcn) shows an excellent selectivity for oxidation of the aromatic ring over the aliphatic site chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toluene was oxidized to para ‐cresol in 22% yield, together with ortho ‐cresol and methyl‐ para ‐benzoquinone in 8 and 1% yield, respectively (Table 3, entry 3). Recent studies on aromatic oxidations have shown other complexes to be capable of oxidizing the aromatic ring of toluene as well, showing however significant amounts of aliphatic oxidation towards benzyl alcohol or benzaldehyde products [3g,4a,b,e,f] . Remarkably, Mn( tips bpmcn) shows an excellent selectivity for oxidation of the aromatic ring over the aliphatic site chain.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recently reported nickel, copper and cobalt complexes supported by aminopyridine ligands accomplished the oxidation of benzene to phenol in improved yields (29–41%) (Figure 1). [4e–g] …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extremely essential to adopt suitable methods for the industrial manufacture of phenol, which should preferably defeat the shortcomings of the cumene process. Therefore, direct benzene hydroxylation is one of the most efficient ways to produce phenol with a better atom economy. This process mostly occurs via the activation of one of the C–H bonds; however, its higher bond energy (460 kJ mol –1 ) makes that difficult. In recent years, many researchers are thoughtfully exploring the possibility of an efficient methodology by designing new catalysts that are able to perform selective phenol synthesis in a single step from benzene and greener oxidants like O 2 or activated oxygen sources . The efforts through conventional approaches like electrochemical oxidation, photochemical oxidation, and Fenton-type reaction are reported to afford lower yields of phenol with poor selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…As the same ligand behaves as a straightforward mononucleating quadridentate in the copper and nickel complexes (O'Connor et al, 2012;Muthuramalingam et al, 2017Muthuramalingam et al, , 2019a, this led to the question as to whether the coordination is governed by the ligand bite vs the larger ionic radius of Co 2+ vs Cu 2+ /Ni 2+ . This proposal was approached by synthesising the homopiperazine analogue, Phpz, whose ligand has a larger (N2-N2A) bite.…”
Section: Structural Commentarymentioning
confidence: 99%